2012
DOI: 10.1111/j.1600-0897.2012.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Models of Fetal Brain Injury, Intrauterine Inflammation, and Preterm Birth

Abstract: CitationBurd I, Balakrishnan B, Kannan S. Models of fetal brain injury, intrauterine inflammation, and preterm birth. Am J Reprod Immunol 2012; 67: 287-295 doi:10.1111/j.1600-0897.2012 Intrauterine infection and inflammation are known risk factors for brain damage in the neonate irrespective of the gestational age. Infectioninduced maternal immune activation leads to a fetal inflammatory response mediated by cytokines that has been implicated in the development of not only periventricular leukomalacia and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
188
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 220 publications
(199 citation statements)
references
References 69 publications
3
188
1
3
Order By: Relevance
“…Reduced neuronal density can also be the end result of neurotoxicity in the central nervous system due to endotoxemia caused by autogenously induced peritonitis and bacterial translocation from the abdominal cavity to the bloodstream [Burd et al, 2012]. Apoptosis may also be involved in this process of brain injury associated with neuronal death [Gavilanes et al, 2009;Kallapur et al, 2014;Lante et al, 2008;Nitsos, Rees, Duncan, Kramer, Harding, Newnham, & Moss, 2006].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced neuronal density can also be the end result of neurotoxicity in the central nervous system due to endotoxemia caused by autogenously induced peritonitis and bacterial translocation from the abdominal cavity to the bloodstream [Burd et al, 2012]. Apoptosis may also be involved in this process of brain injury associated with neuronal death [Gavilanes et al, 2009;Kallapur et al, 2014;Lante et al, 2008;Nitsos, Rees, Duncan, Kramer, Harding, Newnham, & Moss, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…In rats, oxidative stress and shortage of glutathione occurred in the fetal brain after maternal lipopolysaccharide administration, and these responses may result in neurodevelopmental deficits in the offspring [Burd, Balakrishnan, & Kannan, 2012].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrauterine infection and inflammation are established risk factors for CP. 35 Obesity is a chronic low-grade inflammatory condition, 36 but it is not clear whether maternal obesity-induced inflammation might have adverse effects on the developing human brain. However, a study in offspring of rats fed a high-fat diet during pregnancy found increased inflammation within the brain at birth.…”
Section: Figurementioning
confidence: 99%
“…Intrauterine inflammation leads to a dysregulation of the developing brain, known as fetal inflammatory response syndrome (de Moura, Lisboa, & Passos, 2008), regardless of the gestational age (Burd, Balakrishnan, & Kannan, 2012). The maternal response to lipopolysaccharide (LPS) leads to a fetal inflammatory response mediated by cytokines that has been implicated in the development of a spectrum of neurodevelopmental disorders such as autism and schizophrenia (Meyer, 2011;Meyer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%